Pengaruh Komunikasi Internal terhadap Efektivitas Pelayanan Penyuluh Pertanian dan Dampaknya terhadap Produktivitas Kelompok Tani di Kota Tomohon - Avent Christy Patiro; Fadly Steven Jefry Rumondor (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The importance of the role of internal communication in supporting the effectiveness of extension services and its impact on the productivity of farmer groups, it is necessary to conduct research on the influence of internal communication on the effectiveness of agricultural extension services and its impact on the productivity of farmer groups in Tomohon City. This study aims to analyze the level of effectiveness of internal communication in the Tomohon City Agriculture Service, determine the influence of internal communication on the effectiveness of agricultural extension services, identify the impact of effective extension services on the productivity of farmer groups in Tomohon City. The results of the research analysis are that internal communication in the Tomohon City Agriculture Service is in the fairly good category, Internal communication has a positive and significant influence on the effectiveness of agricultural extension services. The effectiveness of extension services has a significant effect on increasing the productivity of farmer groups. There is a significant indirect influence of internal communication on the productivity of farmer groups through the effectiveness of extension services